Implementasi dan Tantangan Cyber Notary di Era Cyber Society 5.0 - Sefiono, Alauddin Galih (JURNAL PENELITIAN SERAMBI HUKUM, 2026)
The rapid development of information technology in the era of Cyber Society 5.0 has driven various professions, including the notarial profession, to undergo digital transformation. One form of this transformation is the emergence of the concept of the Cyber Notary, where notaries perform their duties and exercise their legal authority by utilizing digital technology. This article aims to analyze the implementation and challenges of the Cyber Notary in Indonesia based on existing legal regulations, particularly the Notary Act (UUJN) and the Electronic Information and Transactions Law (UU ITE). Using a normative legal research method, this article reveals that although the UUJN has acknowledged the existence of the Cyber Notary in a normative sense, its regulatory provisions remain limited and have not yet been fully integrated. This creates legal uncertainty in the implementation of digital notarial services, especially concerning the validity of authentic deeds made electronically. In addition, other major challenges include the lack of harmonization among existing regulations, potential digital security breaches, and the need to redefine the term "in person" within the context of digital notarial practice. Therefore, a comprehensive regulatory reform is necessary to ensure legal certainty and the protection of the rights of both the public and notaries in the digital era.